THU0292 Ct- Guided Disco–Vertebral Biopsy in the Diagnosis of Infectious Spondylodiscitis. (10th June 2014) - Ben Abdelghani, K.; Slouma, M.; Souabni, L.; Kassab, S.; Chekili, S.; Laatar, A.; Zakraouui, L.
Abstract : Background: Infectious spondylodiscitis is a common cause of febrile back pain. CT- guided disco-vertebral biopsy (DVB) can provide the diagnosis of infectious spondylodiscitis and facilitate the identification of the causative micro-organism. DVB is considered as the main investigation for etiologic diagnosis. Objectives: The aim of this study was to evaluate the contribution of CT-guided DVB in the diagnosis of infectious spondylodiscitis in Tunisia. Methods: A retrospective study effectuated in the department of Rheumatology in Tunisia between 1995 and 2013. We reviewed the medical records of all patients diagnosed with infectious spondylodiscitis and who underwent DVB. Results: CT-guided DVB was performed in 36 patients leading to the diagnosis in 22 cases (61%). DVB was practiced in 23 patients with tuberculous spondylodiscitis and it confirmed diagnosis in 12 cases. Histological examination showed a giganto-cellular granuloma in all cases. Caseous necrosis was noted in only 4 cases and alcohol resistant bacillus was isolated in 2 cases. CT-guided DVB was performed in 10 cases of pyogenic spondylodiscitis. The causative agent was isolated in all cases. Bacteriological tests revealed two germs in two cases. The micro-organism identified was: Staphylococcus in 4 cases, Grams negative germs in 5 cases and streptococcus in 3 cases. In brucella spondylodiscitis, DVB was performed in 3 and showed a non specific remodeling in all cases. The diagnosis of brucella spondylodiscitis was established basing on clinical, radiological and bacteriological features especially Wright's serologic test. The DVB wasn't conclusive in 14 cases, showing non-specific inflammation. All patients underwent adapted antibiotics. Conclusions: As the treatment of infectious spondylodisctis is based on appropriate antibiotic therapy, the identification of the causative micro-organism is necessary. Our study showed that DVB was frequently conclusive in pyogenic infection. However, in tuberculous and brucella spondylodiscitis, clinical, biological and radiological data are as important as the DVB. References: N. Hopkinson, J. Stevenson, S. Benjamin. A case ascertainment study of septic discitis: clinical, microbiological and radiological features. Q J Med 2001; 94: 465-470. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5458